Fabrication and study of thin transparent conductive films prepared by Spin Coating from metal nano-wires (2016)
(Eng) Transparent conductive thin films on glass substrates from metal nano-wires were produced by the spin coating method by varying the speed of rotation between 1000 and 9000 RPM. Morphological and structural properties of the deposited layers were studied by Scanning Electron Microscopy (SEM). The electrical and optical properties were studied as a function of layer thickness by the Van Der Paw method and transmittance measurements in the range between 350 and 800 nm. A correlation between the thickness of the deposited layers and their electrical and optical properties is obtained, showing less sheet resistance to larger thickness while its transmittance decreases. Samples with sheet resistance of about 20 Ω/sq and with average 77% light transmittance at 550 nm were obtained.